VUV detection in large-area avalanche photodiodes as a function of temperature - Lopes, J. A. M. (2003)
The response of a Peltier-cooled large-area avalanche photodiode to VUV-light is investigated as a function of the operation temperature. The reduction of the temperature down to 5°C will improve both photodiode light-level detection limit and statistical fluctuations; further temperature reduction will not result in improved performance. Optimum operation characteristics are already achieved for gains around 100 and do not depend significantly on the operation temperature. The relative variation of the gain with temperature increases with the biasing voltage presenting values that are almost a factor of two higher than for visible light detection.